Una aproximación a la coquetería femenina ateniense (Estudios humanísticos. Geografía, historia y arte, 2021)
We considerer feminine costume in Classical Greece with a double aspect: Firstly, to serve for the same thing for which it was made (sometimes with important sight of coquetry and as demostration of familiar economic power); secondly, to be a part of the payment (making domestic garment) demanded of women by a society that never appreciated the femenine work correctly. In both occasions the women could dispose of many elements but not every women, for economic or moral reasons, could make use of them